2021
DOI: 10.1177/15569845211000332
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Versus Sternotomy for Mitral Surgery in the Elderly: A Systematic Review and Meta-Analysis

Abstract: Objective The safety of minimally invasive mitral valve surgery (MIMVS) in elderly patients is still debated. Our objective was to perform a systematic review and meta-analysis of studies comparing MIMVS with conventional sternotomy (CS) in elderly patients (≥65 years old). Methods We searched PubMed, EMBASE, Web of Science, clinicaltrials.gov, and Cochrane Central Register of Controlled Trials for trials and observational studies comparing MIMVS with CS in patients ≥65 years old presenting for mitral valve su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
(34 reference statements)
1
8
0
Order By: Relevance
“…In this retrospective analysis, we observed that setting up a program dedicated to the incorporation of mini-thoracotomy for MVr has made it possible to change the management standard in an efficient and controlled manner without significant increases in complication rates. As shown by many groups, the benefits of minimally invasive MVr can be shorter postoperative ventilation times and shorter overall hospital stay without increased postoperative complications, and at similar procedural costs compared to the sternotomy approach (12)(13)(14)(15). Our results are in line with these previous studies, showing significantly decreased postoperative ventilation time and hospital length of stay.…”
Section: Minimally Invasive Mitral Valve Repairsupporting
confidence: 90%
“…In this retrospective analysis, we observed that setting up a program dedicated to the incorporation of mini-thoracotomy for MVr has made it possible to change the management standard in an efficient and controlled manner without significant increases in complication rates. As shown by many groups, the benefits of minimally invasive MVr can be shorter postoperative ventilation times and shorter overall hospital stay without increased postoperative complications, and at similar procedural costs compared to the sternotomy approach (12)(13)(14)(15). Our results are in line with these previous studies, showing significantly decreased postoperative ventilation time and hospital length of stay.…”
Section: Minimally Invasive Mitral Valve Repairsupporting
confidence: 90%
“…Several studies have described the superiority of MIMVS compared to FS, due to a reduction in operative trauma, especially in elderly patients. However, data on MIMVS either mainly focus on low-risk degenerative MV diseases with high MV repair rates [ 8 , 9 , 15 ] or, on secondary MV etiologies. As elderly patients who are frail and have accompanying heart failure more often have complex MV pathologies, MV repairs can sometimes be extremely difficult and harmful, pushing many surgeons to opt for straightforward MV replacement or even reject surgery altogether.…”
Section: Discussionmentioning
confidence: 99%
“…However, the benefits of MIMVS in elderly patients and data on transcatheter interventions are inconclusive. Some investigations have demonstrated that MIMVS reduces operative trauma, with long-term survival at five and seven years of 55% and 52%, respectively [ 8 , 9 , 15 ]. Patients who are considered unsuitable for MT undergo operation with conventional FS.…”
Section: Introductionmentioning
confidence: 99%
“…Endoscopic MVS, which developed as an alternative to full-sternotomy, is traditionally performed in younger patients with low surgical risk. Nevertheless, in addition to transcatheter mitral valve repair strategies (e.g., TEER), minimally-invasive endoscopic MVS, may represent a potential therapeutic option for elderly patients ( 10 ).…”
Section: Discussionmentioning
confidence: 99%